CLINICAL AND RADIOLOGIC APPROACH TO PROBABLE MIXED DEMENTIA (VASCULAR DEMENTIA AND PROGRESSIVE SUPRANUCLEAR PALSY) - Lastri, Diatri Nari; Alwahdy, Ahmad Sulaiman (Malang Neurology Journal, 2020)
Dementia as a global burden neurodegenerative disease need to be diagnosed as earlier as possible then treated accordingly. The varying aetiologies of dementia render specific diagnosis of dementia challenging. Other than clinical syndromes, cognitive function examination and neuroimaging are also important to determine the correct dementia diagnosis. This paper aims to provide a dementia case where the working diagnosis could not be decided at once and to show how cognitive function examination and neuroimaging are essential to determine the diagnosis. This paper reports an 80-year old male with dementia symptoms that was followed and regularly examined for one year. With time, additional neurological symptoms were observed thus the working diagnosis was established. The patient was diagnosed with mixed dementia that consisted of probable vascular cognitive impairment and probable progressive supranuclear palsy.